Impact of Psychological Empowerment (PE) on Organizational Citizenship Behavior (OCB) among the Employees of the National Social Security Fund of Laghouat, Algeria - Hamdi, Abouelkacem (Jordan Journal of Business Administration, 2019)
This study aims at comprehending the impact of psychological empowerment (PE) on organizational citizenship behavior (OCB) among the employees of the National Social Security Fund of Laghouat, Algeria. The sample of the study consists of 137 respondents. The researcher relied on descriptive statistical analysis, multiple regression analysis, correlation coefficients, simple variance analysis and normality distribution test. The study revealed some results with the most important as follows: a high level of (PE) was found among employees with recorded high rates concerning two dimensions: significance and competency on one hand and autonomy on the other. Nevertheless, an intermediate level was recorded in the influence dimension. For OCB, the study resulted in a high level in this variable in general (altruism, courtesy, civic virtue, consciousness and sportsmanship). For the main finding, the researcher has found out that there is a statistically significant impact of all dimensions of (PE) on OCB except for autonomy. Competency has the highest impact, followed by significance; however, it has been observed that there are statistically significant differences between the means of (PE) referred to experience factor, but no statistically significant differences were found between the means of (PE) and OCB ascribed to the rest of factors: sex, age, schooling level and hierarchical level. Finally, the researcher recommends the following suggestions: firstly, focusing on training and continuous learning to raise the level of employees’ competency. Secondly, valuing OCB by including it in the standards for promotion. Thirdly, focusing on the incentive approach and enriching jobs with more challenges and experiences.